Cognitive-cultural, individual-psychological and age particularities of the ability to recognize emotions - Ekaterina Hvorova (Problemy Wczesnej Edukacji)
This article describes the features of the development of the emotional sphere. It emphasizes the importance of the primary school age in the development of certain components of emotional intelligence, one of which is the ability to recognize emotions. In the early school years, children are able to understand emotions, but mostly with the help of their own emotional experience and/ or according to the situations they are used to experiencing, they mostly rely on the context of the situation, and, as we know, it does not always work correctly: different people in the same situations may experience completely different emotions. Few children are able to establish the reasons that caused other people emotions. Besides, one of the components of emotional intelligence is the ability to control one’s own emotions. Emotion regulation becomes available for children after the socialization associated with the first years at school. Child development is partly determined by the process of socialization, which determines specific cognitive representations of emotions, so called emotional prototypes. Also the culture in which the child grows up has effects on the process of emotion recognition and expression, so, for example, in the individualistic culture emotional expression and recognition is encouraged, and in collectivist cultures, there are certain rules of emotional expression fixing in which situations and to what extent the expression of emotions is permissible.